A Mixed-Methods Pilot Study of Student Athlete Engagement in LGBTQ Ally Actions - Toomey, Russell B.; McGeorge, Christi R.; Carlson, Thomas S. (Journal of Intercollegiate Sport, 2016)
Reports of sexual prejudice and heterosexism in sports are still pervasive, despite growing acceptance of lesbian, gay, bisexual, transgender, and queer (LGBTQ) persons in the U.S. Yet, few studies have investigated how and why college studentathletes engage in LGBTQ-focused ally actions (e.g., standing up and speaking out against sexual prejudice; showing support at LGBTQ events). This mixed-methods pilot study describes the development and psychometric testing of the Engagement in LGBTQ Ally Actions in Sports Scale, in addition to analyses of two open-ended questions that provided supplementary insight into what it means to collegiate athletes to be an ally to the LGBTQ community. The convenience sample included 159 college student-athletes from two public universities (M age = 20.67 years, SD = 1.56). Findings indicated that the Engagement in LGBTQ Ally Actions in Sports Scale demonstrated strong internal consistency, validity, and equivalence across gender. Qualitative analyses suggested that college student-athletes define being an ally to the LGBTQ community as involvement in advocacy behaviors and supporting LGBTQ teammates; yet, important gender differences emerged in these findings.